Assessing the Influence of Corporate Social Responsibility on Green Logistics Management of Enterprises in Vietnam - Lu Phi Nga; Phan Thanh Tam (Ianna Journal of Interdisciplinary Studies)
Background: Green logistics supply management aims to achieve the goal of greening the economy, which is a global issue and goal for all countries. This is also the basis for implementing green logistics development in Vietnam.